2006
DOI: 10.1086/503038
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Disease: A Descriptive Study of 228 Patients Hospitalized in a 4-County Region of Colorado in 2003

Abstract: Persons with diabetes and a reported history of alcohol abuse and older persons appear to be at increased risk of developing WNE. Patients with WNE who have a history of stroke, who require mechanical ventilation, or who are immunosuppressed appear to be more likely to die. Respiratory failure, limb weakness, and arrhythmia occurred in all 3 categories, but there were significantly more cases of all in the WNE group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 11 publications
3
145
1
Order By: Relevance
“…Many of the previously conducted studies examined factors associated with the most severe outcomes (e.g., encephalitis with muscle weakness and death) among cohorts of hospitalized patients. 1,7,[14][15][16] These studies generally included small numbers of patients, limiting power to detect associations. Two previous studies evaluated risk factors for neuroinvasive disease among all WNV disease cases reported to state health departments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the previously conducted studies examined factors associated with the most severe outcomes (e.g., encephalitis with muscle weakness and death) among cohorts of hospitalized patients. 1,7,[14][15][16] These studies generally included small numbers of patients, limiting power to detect associations. Two previous studies evaluated risk factors for neuroinvasive disease among all WNV disease cases reported to state health departments.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, cerebrovascular disease, renal disease, and diabetes also have been identified as possible risk factors for severe WNV disease. 1,[5][6][7][13][14][15][16] However, findings have been inconsistent between previous studies, and many of these studies were performed on cohorts of hospitalized patients with relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 98%
“…In 2003, we enrolled a cohort of patients (original Colorado cohort) hospitalized with acute WNV disease at 17 institutions in northern Colorado (N = 221). 16 A participant's WNV clinical syndrome was classified as fever (i.e., non-neuroinvasive disease), meningitis, or encephalitis, with or without AFP based on their presenting signs and symptoms and a follow-up assessment completed by a neurologist (JJS). If a participant was diagnosed with 1 clinical syndrome, we classified them as having the most severe presentation for the purpose of this report (severity: fever meningitis encephalitis AFP).…”
Section: Methodsmentioning
confidence: 99%
“…In a few studies, the involvement of thalamic and midbrain structures are shown in the patients who had WNV encephalitis and stroke [1,6,7]. In a large study of 228 patients infected with WNV in serum it was found that prior history of stroke correlated with increased mortality, however, none of these patients suffered an acute stroke during their hospitalization [8]. To our knowledge, there are only three known cases of stroke in the patients with acute WNV infection, and ours is the first report of isolated pontine stroke complicating WNV meningitis.…”
Section: Discussionmentioning
confidence: 99%